Pengaruh Independensi Auditor, Komitmen Organisasi, Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Auditor (Studi Empiris pada Kantor Akuntan Publik di Wilayah Semarang dan Surakarta) - Risfandhani, Rifqi, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
This study aims to determine the effect of auditor independence, organizational commitment, leadership style and organizational culture on the performance of auditors (Empirical Study at public accounting firms in the region Semarang and Surakarta). This research is quantitative. The method used in collecting data in this study a questionnaire, observation, and library research (documentation). The sample in this study is the auditors who work in public accounting firms in the area of Semarang and Surakarta total of 35 auditors in seven public accounting firms. Testing the hypothesis in this research is the multiple linear regression analysis. The results show the independence of auditors, organizational commitment, leadership style and organizational culture on positive and significant effect on the performance of auditors. Based on F test results show the independence of auditors, organizational commitment, leadership style and organizational culture on performance auditors already fit of goodness or fit. Based on test results that the coefficient of determination R2 adjusted R2 shows variation Auditor performance is affected by the auditor's independence, organizational commitment variable, the variable of leadership style and organizational culture variables.